Mindfulness-based programmes to reduce stress and enhance well-being at work: a realist review - Jeremy Howick; Geoff Wong; Katrin Micklitz (BMJ Open)
Objectives To understand how and why workplace mindfulness-based programmes (MBPs) work or do not work.Design A realist review.Eligibility criteria for selection We considered any studies (experimental quasi-experimental, observational, qualitative and mixed-methods studies) of workplace MBPs as long as they provided data to explain our programme theories. All MBP formats and delivery modes were included.Analysis Consistent with realist review methodology, we systematically screened and analysed data to explain how and why workplace MBPs work or do not work. These explanations were consolidated into a programme theory augmented by theories from organisational literature, such as conservation of resources theory.Results Findings from 75 primary studies suggest that workplace MBPs enable participants (including healthcare professionals) to deal more skillfully with stressful events and improve their well-being. The mechanisms involved can be grouped around awareness/self-regulation, acceptance/compassion, feeling permitted to take care of self, sense of growth and promise of goal attainment. In order for professionals to invest in an MBP and benefit from it, it is important that they feel safe to engage with self-care at work and share emotional difficulties among peers. It is also important that employees are able to link the programme and its activities to existing goals and practices. Concerns of being non-productive, of not getting work done or of being exposed in front of colleagues can result in strategic use of brief mindfulness exercises, non-adherence or drop-out.Conclusions Simply offering an MBP to (healthcare) professionals in order to reduce stress and enhance well-being does not suffice. A supportive environment must exist in order for the programme’s benefits to be reaped.PROSPERO registration number CRD42018086280.